The Need for Monetary Financing of Corona Budget Deficits - Paul De Grauwe (Intereconomics)
Abstract Sooner or later, the ECB must accept that monetary financing in support of deficit spending is a necessity not just for mitigating the coronavirus crisis, but also for averting a downward deflationary cycle that could pull the eurozone apart.